2004
DOI: 10.1051/apido:2004035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-wintering and wintering temperature regimes on weight loss, survival, and emergence time in the mason bee Osmia cornuta (Hymenoptera: Megachilidae)

Abstract: -Osmia cornuta adults require exposure to wintering temperatures followed by incubation in the spring to emerge. We studied winter survival, weight loss, emergence time, and post-emergence longevity in O. cornuta exposed to a variety of pre-wintering and wintering treatments. Few bees emerged after exposure to wintering durations <30 days. Maximum survival and longevity were obtained with wintering durations of 90-150 days. Time to emergence following incubation declined with increasing wintering duration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
96
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 32 publications
6
96
0
1
Order By: Relevance
“…The duration of the wintering period and wintering temperature are important factors influencing the emergence time (Bosch & Blas, 1994;Bosch & Kemp, 2003;Sgolastra et al, 2010). Wintering temperature ceases to be significant when wintering lasts longer than 120 days (Bosch & Kemp, 2004). Wintering in controlled conditions eliminates these factors and creates comparable conditions for insects in all test groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The duration of the wintering period and wintering temperature are important factors influencing the emergence time (Bosch & Blas, 1994;Bosch & Kemp, 2003;Sgolastra et al, 2010). Wintering temperature ceases to be significant when wintering lasts longer than 120 days (Bosch & Kemp, 2004). Wintering in controlled conditions eliminates these factors and creates comparable conditions for insects in all test groups.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence time of insects depends on the developmental temperature in the pre-wintering and wintering periods and on the duration of wintering. Both factors are related to the metabolism of reserves (Bosch & Kemp, 2003, 2004Bosch, Kemp, & Peterson, 2000;Sgolastra et al, 2010;Radmacher & Strohm, 2011). In Osmia lignaria, increasing the temperature to 26˚C in the prepupal and pupal stages shortened the emergence time of imagines in the spring (Kemp & Bosch, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the economic utilization of reserves during overwintering is necessary. Several observations performed in O. lignaria and Osmia cornuta indicated that longer pre-wintering period or exposure to milder winter temperatures increased fat body depletion and probably utilization of energy substrates (Bosch and Kemp 2004;Bosch et al 2010;Sgolastra et al 2010). An early consumption of reserves would disrupt emergence from the cocoon, flying to the nearest flowers to sip nectar or even nesting (Bosch and Vicens 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For pollination purposes, it is advisable to maximize the number of females in the progeny and to produce large individuals that have a higher fecundity (e.g., Tepedino and Torchio 1989;Kim 1997;Tomkins et al 2001;Bosch and Vicens 2006), lower winter mortalities (Tepedino and Torchio 1982;Bosch and Kemp 2004), and can be expected to work at cooler temperatures (Stone and Willmer 1989;Stone 1994). On the other hand, building costs of nest structures such as brood cell lining and partitions have to be minimized.…”
Section: Introductionmentioning
confidence: 99%